Emerging and Priority Pollutants in Rivers Bringing Science into River Management Plans - Guasch, Helena.; Guasch, Helena.; Ginebreda, Antoni.; Ginebreda, Antoni.; Geiszinger, Anita.; Geiszinger, Anita. (The Handbook of Environmental Chemistry,, 2012)
The enduring changes in the aquatic environment and the increasing influx of contaminants call for novel conceptual and methodological approaches to relating chemical pollution and ecological alterations in ecosystems. This volume highlights the latest advances concerning the sampling, analyses, occurrence, bioavailability, and effects of emerging and priority pollutants in European rivers, the current status of the River Management Plans in Europe, and the applicability of the newly developed techniques for water monitoring purposes. The topics are discussed in the context of the EU Water Framework Directive, evaluating their shortcomings and providing a basis for doing away with them. Linking scientific research and river management practices, this book is an invaluable source of information for environmental chemists, aquatic scientists, ecologists and water managers.